Hungarian Monitoring, 26 September 1989 . [Magyar rádiófigyelő], 1989. szeptember 26 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Soviet foreign minister reacts to Bush's proposal to reduce chemical weapons - Weighing up Soviet-American foreign ministers' meeting - Last Vietnamese soldier leaves Cambodia today - Shevardnadze's speech at UN general assembly - A bag of rice for a kilo of raw opium: new opportunity at the Soviet-Afghan border region - Situation in Peking in view of new general secretary's speech Domestic Affairs: - Autumn session of Parliament opens with participation of opposition representatives - Public debate at the Hungarian Academy of Sciences - Leaders of MTI, RFE and Radio Liberty continue discussions Economy: - Hungarian government proposes that European Community ease entry of Hungarian products to territory of the Common Market - Ferenc Bartha on Hungarian position at World Bank and IMF joint meeting - Gabčíkovo-Nagymaros construction Külpolitika: - A szovjet külügyminiszter reakciója Bush vegyi fegyver csökkentési javaslatára - A szovjet-amerikai külügyminiszteri találkozó mérlege - Ma az utolsó vietnámi katona is elhagyja Kambodzsát - Sevardnadze felszólalása az ENSZ közgyűlésen - Egy zsák rizsért egy kg. nyers ópium - Új lehetőség a szovjet-afgán határtérségben - Pekingi helyzetkép az új főtitkár beszéde tükrében Belpolitika: - Ellenzéki képviselők részvételével megkezdődött az Országgyűlés őszi ülésszaka - Nyilvános vita volt a MTA székházában - Tárgyalást folytattak az MTI, a SZER és a SZABADSÁG RÁDIÓ vezetői Gazdaság: - A magyar kormány javasolja, hogy az Európai Közösség könnyítse meg a magyar áruk bejutását a K.P. területére - Világbank és; a Nemzetközi Valutaalap közgyűlésén Bartha Ferenc a magyar tárgyalási álláspontról - A Bős-nagymarosi építkezés